2006
DOI: 10.1590/s1806-83242006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic alterations in the oral mucosa after chronic exposure to ethanol

Abstract: The effects of ethanol alone on the oral mucosa are still poorly understood, especially because there are few non-smoking chronic consumers of alcoholic beverages. The aim of this study was to evaluate the frequency of micronucleus, abnormal nucleus/cytoplasm ratio, pyknosis, karyorrhexis and karyolysis in exfoliated cells from the buccal mucosa and from the lateral border of the tongue in 36 non-smoker alcoholics (ethanol group) and 18 non-smokers and non-drinkers (control group). The Papanicolaou method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
2
19
1
3
Order By: Relevance
“…Esse relato confi rma o que é de conhecimento geral na literatura, que o uso simultâneo desses dois fatores aumenta consideravelmente o risco de desenvolvimento dessas lesões, como também delas se transformarem em um câncer, devido ao efeito sinérgico e da relação dose-dependente dos mesmos 22 . A ação carcinogênica do álcool na mucosa oral comumente se dá quando a ingestão diária de etanol é superior a 45 ml 23 , a qual depende da concentração, duração, frequência e associação com outros agentes carcinogênicos 22 . No presente estudo, é demonstrado maior quanti dade de eti listas consumindo bebidas fermentadas e com consumo de até 1 litro, independente da frequência de uso, confrontando com o estudo de Fernandes et al 22 , que evidenciou maior parte no uso de bebidas desti ladas e com consumo de 10 a 20 litros/ano.…”
Section: Discussionunclassified
“…Esse relato confi rma o que é de conhecimento geral na literatura, que o uso simultâneo desses dois fatores aumenta consideravelmente o risco de desenvolvimento dessas lesões, como também delas se transformarem em um câncer, devido ao efeito sinérgico e da relação dose-dependente dos mesmos 22 . A ação carcinogênica do álcool na mucosa oral comumente se dá quando a ingestão diária de etanol é superior a 45 ml 23 , a qual depende da concentração, duração, frequência e associação com outros agentes carcinogênicos 22 . No presente estudo, é demonstrado maior quanti dade de eti listas consumindo bebidas fermentadas e com consumo de até 1 litro, independente da frequência de uso, confrontando com o estudo de Fernandes et al 22 , que evidenciou maior parte no uso de bebidas desti ladas e com consumo de 10 a 20 litros/ano.…”
Section: Discussionunclassified
“…The higher incidence of carcinoma of the oral cavity in male patients can be attributed to their higher consumption of alcohol and tobacco (Johnson 2001;Reis, do Espirito Santo et al 2006). It was also shown that probably due to their increased tobacco consumption the latter showed a signiWcantly lower BMI than the case group (Molarius et al 1997;Bamia et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MN evaluations are made in buccal epithelial exfoliated cells (BEC) as well, and this test is considered to be the least invasive method available with which to measure DNA damage in humans. 5 As a result of its ability to assess the activity of many chemical or physical carcinogenic and mutagenic agents in situ, the MN test in the BEC is the choice of many recent human biomonitoring studies, including those involving the following: alcohol, 6 tobacco, 7 oral cancer and other oral pathologies, 8 and patients undergoing radiotherapy 2 or chemotherapy. 9 With regard to ionizing radiation in dentistry, the MN test in the BEC was utilized to evaluate the panoramic dental radiograph, 3,[10][11][12][13][14][15][16] the lateral digital radiograph, 17 mandibular cone beam computed tomography (CBCT), 18 and orthodontic radiographs.…”
Section: Introductionmentioning
confidence: 99%